A relação entre as noções de transvaloração e além-do-homem nos escritos de maturidade de Friedrich Nietzsche - Porfírio Neto, Francisco José (2018)
The purpose of this text is to analyze the notions of revaluation of moral values and superman in the work of maturity of Friedrich Nietzsche, with a hypothesis that there is a relation between these two concepts, We deal with themes that form part of the scene that composes Nietzsche's work, especially the notions of value, nihilism and the inversion of moral values. We have done a survey of the occurrences of the keywords of this work to expose, from each book, how Nietzsche understands the superman and how he understands the notion of revaluation of values at different moments of his writing. With this, we pointed out in the section of Thus Spoke Zarathustra, titled On Old and New Tables of Value, the connection between the concepts of superman and the revaluation of values.